Hydration and Orientation of Carbonyl Groups in Oppositely Charged Lipid Monolayers on Water - Dreier, L. B. (J Phys Chem B, 2019)
[Image: see text] The carbonyl groups of glycerolipid monolayers on water play an important role in the formation of the interfacial hydrogen bond network, which in turn influences the interactions of lipids with, for example, metabolites. As the frequency of the carbonyl absorption band strongly depends on the hydration state of the lipid headgroups, the carbonyl band is a sensitive reporter of changes in the headgroup environment. Here, we use phase-resolved sum frequency generation spectroscopy to obtain information about the orientation and hydration of the carbonyl groups in lipid monolayers. We find that there are two distinct carbonyl moieties in the lipid monolayers, oppositely oriented relative to the surface plane, that experience substantially different hydrogen-bonding environments.